The effect of compensation suitability, internal control, accounting information systems, and management morality on fraud prevention (study on Fox Hotel Pekanbaru City) - Permata, Nella; Ramashar, Wira (JAAF (Journal of Applied Accounting and Finance), 2024)
This research is a quantitative study with the research objective to examine the effect of internal control, accounting information systems, management morality and compensation conformity on fraud prevention. The population in this study were front office and back-office employees at Fox Hotel Pekanbaru City. This study uses primary data collected using a questionnaire. In this study the sample amounted to 30 respondents selected using purposive sampling. Data analysis in this study used multiple linear regression analysis. The results of this study indicate that internal control, accounting information systems, management morality and compensation conformity have a significant effect on fraud prevention.